Chiral segregation driven by a dynamical response of the adsorption footprint to the local adsorption environment: bitartrate on Cu(110). Issue 11 (2nd March 2017) - Darling, G. R.; Forster, M.; Lin, C.; Liu, N.; Raval, R.; Hodgson, A.
Abstract : Bitartrate, a strongly bound chiral modifier, is able to restructure its adsorption footprint on Cu(110) in response to local adsorbates. Abstract : Local or global ordering of chiral molecules at a surface is a key step in both chiral separation and heterogeneous enantioselective catalysis. Using density functional theory and scanning probe microscopy results, we find that the accepted structural model for the well known bitartrate on Cu(110) chiral system cannot account for the chiral segregation observed. Instead, we show that this strongly bound, chiral adsorbate changes its adsorption footprint in response to the local environment. The flexible adsorption geometry allows bitartrate to form stable homochiral trimer chains in which the central molecule restructures from a rectangular to an oblique footprint, breaking its internal hydrogen bonds in order to form strong intermolecular hydrogen bonds to neighbouring adsorbates. Racemic structures containing mixed enantiomers do not form strong hydrogen bonds, providing the thermodynamic driving force for the chiral separation that is observed experimentally. This result shows the importance of considering the dynamical response of molecular adsorption footprints at the surface in directing chiral assembly and segregation. The ability of strongly-chemisorbed enantiomers to change footprint depending on the local adsorption environment indicates that supramolecular assemblies at surfaces may exhibit more complex dynamical behaviour than hitherto suspected, which, ultimately, could be tailored to lead to environment and stimuli-responsive chiral surfaces.